Pancreatic cystic lesions: comparison of preoperative cytological results by eus-fna with surgical pathologist diagnosis - Tsimperleniou, Maria; Karoumpalis, Ioannis; Marvaki, Christina; Kadda, Olga; Exarchos, Dimitrios; Lutrari, Eleni (Health & Research Journal, 2016)
Introduction: The preoperative cytological examination of pancreatic cystic lesions with endoscopic ultrasound and fine needle aspiration biopsy [Endoscopic Ultrasonography (EUS)-Fine Needle Aspiration (FNA)] is of great importance for avoiding unnecessary surgery. Aim: The aim of the present study was to show the importance of EUS-FNA in patients with cystic pancreatic lesions by comparing its results with surgical pathology diagnosis, intending by the selection of appropriate patients for surgery, to reduce preoperative morbidity and mortality and long duration of hospitalization conditions which are responsible for hospital infections as well as public health costs. Material and Methods: This was a prospective observational study. The studied sample consisted of 40 patients with pancreatic cysts. For data collection a specific registration form was used; the demographic characteristics, imaging methods and their results, the symptoms, any previous episodes of pancreatitis, the visualization with EUS, cytological analysis of fluid of pancreatic cysts, and CEA levels and fluid amylase, whenever was possible, as well as the pathologist results of the resected lesions were recorded. Data analysis was performed with the Statistical Package for Social Sciences (SPSS). Results: The sample included 40 patients, 17 men (42.5%) and 23 women (57.5%). The overall operating characteristics of EUS-FNA for pancreatic lesions which were resected, were as follows: sensitivity specificity 81.8% 100.0%, positive predictive value of 100%, negative predictive value 66.0% and 86.7% diagnostic accuracy. Conclusions: The present study confirmed that the EUS-FNA is the method which has high accuracy to select the appropriate patients with pancreatic cystic lesions for therapeutic pancreatectomy.